Partial isolated rupture of the popliteus tendon in a professional soccer player: a case report - Mariani, P.; Margheritini, P. (Sports Medicine, Arthroscopy, Rehabilitation, Therapy & Technology (SMARTT), 2009)
The complete isolated rupture of the popliteus tendon has been described as a rare injury and this report describes the case of a 31-year-old soccer player who sustained a partial rupture of the popliteus tendon during a game. The injury was suspected clinically and at MRI but confirmed only by the arthroscopic examination. The treatment consisted in open debridment with no tendon repair or augmentation. Seven weeks post-operation the patient was symptom-free and returned to competitive professional soccer at the same preinjury level. The clinical and arthroscopic findings of the case reported suggest a possible overuse disease with degenerative expression.